Assessment of burnout, resilience, and thriving among academic health professionals: findings from an international study - Nahas, Abdul Rahman Fata; Elnaem, Mohamed Hassan; Mubarak, Naeem; Abou Khatwa, Merna; Barakat, Muna; Faller, Erwin Martinez; M. Kassem, Lamyaa; Ramatillah, Diana Laila; Jaber, Ammar; Akkawi, Muhammad Eid; Mohammed Al-Shami, Abdulkareem; Chandran, Sarath; et al. (Frontiers, 2024)
Introduction: Burnout, resilience, and thriving significantly impact academics, particularly in health professions, where responsibilities are extensive. This study aimed to explore these constructs among academic health professionals, examining sociodemographic and work-related factors influencing these outcomes.